Acceptance Tests of more than 10 000 Photomultiplier Tubes for the multi-PMT Digital Optical Modules of the IceCube Upgrade - Abbasi, R.; Ackermann, M.; Adams, J.; Agarwalla, S. K.; Aguilar, J. A.; Ahlers, M.; Alameddine, J. M.; Amin, N. M.; Andeen, K.; Anton, Gisela; Argüelles, C.; Ashida, Y.; et al. (Journal of Instrumentation, 2024)
More than 10 000 photomultiplier tubes (PMTs) with a diameter of 80 mm will be installed in multi-PMT Digital Optical Modules (mDOMs) of the IceCube Upgrade. These have been tested and pre-calibrated at two sites. A throughput of more than 1000 PMTs per week with both sites was achieved with a modular design of the testing facilities and highly automated testing procedures. The testing facilities can easily be adapted to other PMTs, such that they can, e.g., be re-used for testing the PMTs for IceCube-Gen2. Single photoelectron response, high voltage dependence, time resolution, prepulse, late pulse, afterpulse probabilities, and dark rates were measured for each PMT. We describe the design of the testing facilities, the testing procedures, and the results of the acceptance tests.
CRIS-Team Scopus Importer:2024-08-16
Keywords: Cherenkov detectors; Neutrino detectors; Photon detectors for UV; HPDs; others); visible and IR photons (vacuum) (photomultipliers

Characterization of the astrophysical diffuse neutrino flux using starting track events in IceCube - Abbasi, R.; Ackermann, M.; Adams, J.; Agarwalla, S. K.; Aguilar, J. A.; Ahlers, M.; Alameddine, J. M.; Amin, N. M.; Andeen, K.; Anton, Gisela; Argüelles, C.; Ashida, Y.; et al. (Physical Review D, 2024)
A measurement of the diffuse astrophysical neutrino spectrum is presented using IceCube data collected from 2011-2022 (10.3 years). We developed novel detection techniques to search for events with a contained vertex and exiting track induced by muon neutrinos undergoing a charged-current interaction. Searching for these starting track events allows us to not only more effectively reject atmospheric muons but also atmospheric neutrino backgrounds in the southern sky, opening a new window to the sub-100 TeV astrophysical neutrino sky. The event selection is constructed using a dynamic starting track veto and machine learning algorithms. We use this data to measure the astrophysical diffuse flux as a single power law flux (SPL) with a best-fit spectral index of γ=2.58-0.09+0.10 and per-flavor normalization of φper-flavorAstro=1.68-0.22+0.19×10-18×GeV-1 cm-2 s-1 sr-1 (at 100 TeV). The sensitive energy range for this dataset is 3-550 TeV under the SPL assumption. This data was also used to measure the flux under a broken power law, however we did not find any evidence of a low energy cutoff.
CRIS-Team Scopus Importer:2024-07-19

Citizen science for IceCube: Name that Neutrino - Abbasi, R.; Ackermann, M.; Adams, J.; Agarwalla, S. K.; Aguilar, J. A.; Ahlers, M.; Alameddine, J. M.; Amin, N. M.; Andeen, K.; Anton, Gisela; Argüelles, C.; Ashida, Y.; et al. (European Physical Journal Plus, 2024)
Name that Neutrino is a citizen science project where volunteers aid in classification of events for the IceCube Neutrino Observatory, an immense particle detector at the geographic South Pole. From March 2023 to September 2023, volunteers did classifications of videos produced from simulated data of both neutrino signal and background interactions. Name that Neutrino obtained more than 128,000 classifications by over 1800 registered volunteers that were compared to results obtained by a deep neural network machine-learning algorithm. Possible improvements for both Name that Neutrino and the deep neural network are discussed.
CRIS-Team Scopus Importer:2024-06-28

Exploration of mass splitting and muon/tau mixing parameters for an eV-scale sterile neutrino with IceCube - Abbasi, R.; Ackermann, M.; Adams, J.; Agarwalla, S. K.; Aguilar, J. A.; Ahlers, M.; Alameddine, J. M.; Amin, N. M.; Andeen, K.; Argüelles, C.; Ashida, Y.; Athanasiadou, S.; et al. (Physics Letters B, 2024)
We present the first three-parameter fit to a 3+1 sterile neutrino model using 7.634 years of data from the IceCube Neutrino Observatory on νμ+ν‾μ charged-current interactions in the energy range 500–9976 GeV. Our analysis is sensitive to the mass-squared splitting between the heaviest and lightest mass state (Δm412), the mixing matrix element connecting muon flavor to the fourth mass state (|Uμ4|2), and the element connecting tau flavor to the fourth mass state (|Uτ4|2). Predicted propagation effects in matter enhance the signature through a resonance as atmospheric neutrinos from the Northern Hemisphere traverse the Earth to the IceCube detector at the South Pole. The remaining sterile neutrino matrix elements are left fixed, with |Ue4|2=0 and δ14=0, as they have a negligible effect, and δ24=π is set to give the most conservative limits. The result is consistent with the no-sterile neutrino hypothesis with a probability of 4.3%. Profiling the likelihood of each parameter yields the 90% confidence levels: 2.4eV2<Δm412<9.6eV2, 0.0081<|Uμ4|2<0.10, and |Uτ4|2<0.035, which narrows the allowed parameter-space for |Uτ4|2. However, the primary result of this analysis is the first map of the 3+1 parameter space exploring the interdependence of Δm412, |Uμ4|2, and |Uτ4|2.
CRIS-Team Scopus Importer:2024-11-01
Keywords: Atmospheric neutrino IceCube TeV oscillation sterile

Improved modeling of in-ice particle showers for IceCube event reconstruction - Abbasi, R.; Ackermann, M.; Adams, J.; Agarwalla, S. K.; Aguilar, J. A.; Ahlers, M.; Alameddine, J. M.; Amin, N. M.; Andeen, K.; Anton, Gisela; Argüelles, C.; Ashida, Y.; et al. (Journal of Instrumentation, 2024)
The IceCube Neutrino Observatory relies on an array of photomultiplier tubes to detect Cherenkov light produced by charged particles in the South Pole ice. IceCube data analyses depend on an in-depth characterization of the glacial ice, and on novel approaches in event reconstruction that utilize fast approximations of photoelectron yields. Here, a more accurate model is derived for event reconstruction that better captures our current knowledge of ice optical properties. When evaluated on a Monte Carlo simulation set, the median angular resolution for in-ice particle showers improves by over a factor of three compared to a reconstruction based on a simplified model of the ice. The most substantial improvement is obtained when including effects of birefringence due to the polycrystalline structure of the ice. When evaluated on data classified as particle showers in the high-energy starting events sample, a significantly improved description of the events is observed.
CRIS-Team Scopus Importer:2024-07-12
Keywords: Cherenkov detectors; Neutrino detectors; programs; Simulation methods

Methods and stability tests associated with the sterile neutrino search using improved high-energy νμ event reconstruction in IceCube - Abbasi, R.; Ackermann, M.; Adams, J.; Agarwalla, S. K.; Aguilar, J. A.; Ahlers, M.; Alameddine, J. M.; Amin, N. M.; Andeen, K.; Argüelles, C.; Ashida, Y.; Athanasiadou, S.; et al. (Physical Review D, 2024)
We provide supporting details for the search for a 3+1 sterile neutrino using data collected over 10.7 years at the IceCube Neutrino Observatory. The analysis uses atmospheric muon-flavored neutrinos from 0.5 to 100 TeV that traverse Earth to reach the IceCube detector and finds a best-fit point at sin2(2θ24)=0.16 and Δm412=3.5 eV2 with a goodness-of-fit p value of 12% and consistency with the null hypothesis of no oscillations to sterile neutrinos with a p value of 3.1%. Several improvements were made over past analyses, which are reviewed in this article, including upgrades to the reconstruction and the study of sources of systematic uncertainty. We provide details of the fit quality and discuss stability tests that split the data for separate samples, comparing results. We find that the fits are consistent between split datasets.
CRIS-Team Scopus Importer:2024-11-29

Probing the Connection between IceCube Neutrinos and MOJAVE AGN - Abbasi, R.; Ackermann, M.; Adams, J.; Agarwalla, S. K.; Aguilar, J. A.; Ahlers, M.; Alameddine, J. M.; Amin, N. M.; Andeen, K.; Argüelles, C.; Ashida, Y.; Athanasiadou, S.; et al. (Astrophysical Journal, 2024)
Active galactic nuclei (AGN) are prime candidate sources of the high-energy, astrophysical neutrinos detected by IceCube. This is demonstrated by the real-time multimessenger detection of the blazar TXS 0506+056 and the recent evidence of neutrino emission from NGC 1068 from a separate time-averaged study. However, the production mechanism of the astrophysical neutrinos in AGN is not well established, which can be resolved via correlation studies with photon observations. For neutrinos produced due to photohadronic interactions in AGN, in addition to a correlation of neutrinos with high-energy photons, there would also be a correlation of neutrinos with photons emitted at radio wavelengths. In this work, we perform an in-depth stacking study of the correlation between 15 GHz radio observations of AGN reported in the MOJAVE XV catalog, and 10 yr of neutrino data from IceCube. We also use a time-dependent approach, which improves the statistical power of the stacking analysis. No significant correlation was found for both analyses, and upper limits are reported. When compared to the IceCube diffuse flux, at 100 TeV and for a spectral index of 2.5, the upper limits derived are ∼3% and ∼9% for the time-averaged and time-dependent cases, respectively.
CRIS-Team Scopus Importer:2024-10-11

Search for a light sterile neutrino with 7.5 years of IceCube DeepCore data - Abbasi, R.; Ackermann, M.; Adams, J.; Agarwalla, S. K.; Aguilar, J. A.; Ahlers, M.; Alameddine, J. M.; Amin, N. M.; Andeen, K.; Argüelles, C.; Ashida, Y.; Athanasiadou, S.; et al. (Physical Review D, 2024)
We present a search for an eV-scale sterile neutrino using 7.5 years of data from the IceCube DeepCore detector. The analysis uses a sample of 21,914 events with energies between 5 and 150 GeV to search for sterile neutrinos through atmospheric muon neutrino disappearance. Improvements in event selection and treatment of systematic uncertainties provide greater statistical power compared to previous DeepCore sterile neutrino searches. Our results are compatible with the absence of mixing between active and sterile neutrino states, and we place constraints on the mixing matrix elements |Uμ4|2<0.0534 and |Uτ4|2<0.0574 at 90% CL under the assumption that Δm412≥1 eV2. These null results add to the growing tension between anomalous appearance results and constraints from disappearance searches in the 3+1 sterile neutrino landscape.
CRIS-Team Scopus Importer:2024-11-01

Search for an eV-Scale Sterile Neutrino Using Improved High-Energy νμ Event Reconstruction in IceCube - Abbasi, R.; Ackermann, M.; Adams, J.; Agarwalla, S. K.; Aguilar, J. A.; Ahlers, M.; Alameddine, J. M.; Amin, N. M.; Andeen, K.; Argüelles, C.; Ashida, Y.; Athanasiadou, S.; et al. (Physical Review Letters, 2024)
This Letter presents the result of a 3+1 sterile neutrino search using 10.7 yr of IceCube data. We analyze atmospheric muon neutrinos that traverse the Earth with energies ranging from 0.5 to 100 TeV, incorporating significant improvements in modeling neutrino flux and detector response compared to earlier studies. Notably, for the first time, we categorize data into starting and throughgoing events, distinguishing neutrino interactions with vertices inside or outside the instrumented volume, to improve energy resolution. The best-fit point for a 3+1 model is found to be at sin2(2θ24)=0.16 and Δm412=3.5 eV2, which agrees with previous iterations of this Letter. The result is consistent with the null hypothesis of no sterile neutrinos with a p value of 3.1%.
CRIS-Team Scopus Importer:2024-12-06

Search for Joint Multimessenger Signals from Potential Galactic Cosmic-Ray Accelerators with HAWC and IceCube - Alfaro, R.; Alvarez, C.; Arteaga-Velázquez, J. C.; Avila Rojas, D.; Ayala Solares, H. A.; Babu, R.; Belmont-Moreno, E.; Caballero-Mora, K. S.; Capistrán, T.; Carramiñana, A.; Casanova, S.; Cotti, U.; et al. (Astrophysical Journal, 2024)
The origin of high-energy galactic cosmic rays is yet to be understood, but some galactic cosmic-ray accelerators can accelerate cosmic rays up to PeV energies. The high-energy cosmic rays are expected to interact with the surrounding material or radiation, resulting in the production of gamma-rays and neutrinos. To optimize for the detection of such associated production of gamma-rays and neutrinos for a given source morphology and spectrum, a multimessenger analysis that combines gamma-rays and neutrinos is required. In this study, we use the MultiMission Maximum Likelihood framework with IceCube Maximum Likelihood Analysis software and HAWC Accelerated Likelihood to search for a correlation between 22 known gamma-ray sources from the third HAWC gamma-ray catalog and 14 yr of IceCube track-like data. No significant neutrino emission from the direction of the HAWC sources was found. We report the best-fit gamma-ray model and 90% CL neutrino flux limit from the 22 sources. From the neutrino flux limit, we conclude that, for five of the sources, the gamma-ray emission observed by HAWC cannot be produced purely from hadronic interactions. We report the limit for the fraction of gammarays produced by hadronic interactions for these five sources.
CRIS-Team Scopus Importer:2024-11-29